Удосконалення теорії динаміки і обладнання систем транспортування плівкових матеріалів в лініях пакування харчової продукції - Пригодій, Денис Віталійович (My University, 2018)
Дисертація на здобуття наукового ступеня кандидата технічних наук за спеціальністю 05.18.12 – процеси та обладнання харчових, мікробіологічних та фармацевтичних виробництв (технічні науки). Національний університет харчових технологій Міністерства освіти і науки України. Київ, 2018. В дисертації наведено аналіз особливостей систем транспортування гнучких пакувальних матеріалів, динаміки перехідних процесів, методів дослідження, що стосуються переміщень рулонних матеріалів, характеристик тертя в технологічному обладнанні та вузлах ліній пакування, особливостей навантажень в системах циклічної дії з гнучкими елементами. Особливості тертя і співвідношення між рушійними параметрами та факторами опору оцінювалися на основі класичних положень математичної теорії тертя з пошуками можливостей збільшення і обмеження силових показників останньої. Показано, що сучасна теоретична база синтезу технологічних машин на основі використання плівкових рулонних матеріалів поєднує можливості врахування технологічних та економічних вимог, показників високої продуктивності, умов сусідства, обмеження силових і енергетичних параметрів. Теоретичні і експериментальні розробки доповнені актами їх впроваджень у виробництво та в учбовий процес. Dissertation on the receipt of scientific degree of candidate of engineering sciences after specialty 05.18.12 – processes and equipment of food, microbiological and pharmaceutical productions. National university of food technologies of Department of education and science of Ukraine, Kiev, 2018. In the dissertation the analysis of the features of the systems of transportation of flexible packaging materials, dynamics of transients, methods of research concerning displacements of roll materials, friction characteristics in technological equipment and nodes of packing lines, peculiarities of loads in systems of cyclic action with flexible elements is given. The features of friction and the relationship between driving parameters and resistance factors were evaluated on the basis of the classical provisions of the mathematical theory of friction with the search for possibilities of increasing and limiting the power indicators of the latter. It is shown that the modern theoretical basis for the synthesis of technological machines on the basis of the use of film roll materials combines the possibility of taking into account technological and economic requirements, indicators of high productivity, conditions of neighborhood, limitation of power and energy parameters. Among the positive directions of creating effective systems are synchronized combination of operations, the use of optimal laws for the movement of workers, and so on. The prospects of using parallel streams for increasing productivity and using the runoff regimes for energy recovery are shown. Application of friction working organs prevails in the systems of moving of pellicle materials. Prime price of container in machines with the complete cycle of her making, packing, sealing-in and dating less comparatively with cases the use of red packing. Power charges in the systems of moving of pellicle, roll packing materials are related to work of motive forces against a friction and on creation of streams of kinetic energy of the movable masses.
Keywords: ланцюгова лінія; динаміка; плівкові матеріали; пакування; транспортування; тертя; моменти інерції; закони Амонтона; chain line; dynamics; film materials; packaging; transportation; friction; moments of inertia; Amonton's laws